Rehabilitation of Reinforced Concrete Corner Beam-Column Joints Subjected to Damage. - Aziz, Zana Abdulla; Abdulkadir, Mohamed Raouf (Sulaimani Journal for Pure and Applied Sciences, 2015)
Important structural properties related to strength and deformations of corner beam- column joints damaged and strengthened were studied in this investigation. For this purpose a total of 18 corner beam-column joints divided into five groups were cast and tested. The cross sections were 150mm X 200mm and 150mm X 250mm for the beam and column, respectively. The legs of each beam and column were 900mm. Group1 specimens were consisted of two control specimens tested to failure. Other groups specimens each consisted of four specimens, two of which were tested up to first crack loading and the other two were tested up to 80% of the expected ultimate load. After preloading, the damaged specimens were strengthened in such a way that Group2 were strengthened with strip of CFRP, Group3 with steel plate strip, Group4 with ferrocement, and Group5 with full CFRP sheets. After strengthening process, the strengthened specimens were retested to failure. The test results indicated that the process of the rehabilitations is successful. After strengthening, the ultimate load was increased by 38.3, 4.25, 6.3, and 42.5 % for Group2, 3, 4, and 5, respectively. The stiffness of the strengthened specimens increased compared to the control specimens. The better strengthening technique was those specimens strengthened with full CFRP sheets. The effect of cracking due to preloading on the flexural behavior of strengthened beam- column joint was found to be insignificant.